Knowledge, attitudes and practices regarding evidence-based practice: a cross-sectional study of nurses at Sultan Ahmad Shah medical centre @IIUM (SASMEC @IIUM), Kuantan, Pahang, Malaysia - Ahmad, Norfadzilah; Makhtar, Aniawanis; Abdullah, Nik Aisyah; Mohd Fadzil, Suhaiza (IIUM Press, 2024)
Background: The aim of this study was to assess the knowledge, attitudes and practices (KAP) related to evidence-based practice (EBP) among nurses at Sultan Ahmad Shah Medical Centre @IIUM (SASMEC @IIUM) and to examine the relationship between these factors and socio-demographic characteristics. Methods: A cross-sectional survey was conducted from April to May 2022 among 122 nurses using a structured questionnaire, including the Evidence-Based Practice Questionnaire (EBPQ). The data were analysed using SPSS version 23. Results: The majority of nurses demonstrated moderate EBP knowledge (63.9%), positive attitude (96.7%), and moderate practice level (50%). A significant correlation was found between EBP knowledge and participation in EBP-related programs (p < 0.05). Conclusion: While most nurses at SASMEC @IIUM have moderate EBP knowledge and practice, their attitudes towards EBP are overwhelmingly positive. It is recommended to improve EBP implementation through continuous education and targeted interventions